Mulheres e o exercício da liderança nas Assembleias de Deus no Brasil: uma questão ética - Pontes, Miqueias Machado (2015)
The role of women and exercising leadership has been an issue of ethical discussion in the Assemblies of God in Brazil faced with the challenges imposed by modernity. The concept of otherness and the issues raised by feminism and incorporated in feminist theologies can help in the quest for answers. Some women have stood out in the history of this religious denomination showing that the participation of women in the ecclesiastical pastoral function is possible. The stories of Frida Vingren and Ruth Doris Lemas prove that since the foundation of the Assemblies of God in Brazil up to the consolidation of the formation of their leadership, the women have actively participated and even demanded their recognition through the ministerial ordination. In this discussion gender issues are involved which show possible new perspectives for the future of the church in Brazil. That is why, considering the active and organically distributed role of the women, this conclusion paper for the Professional Master s program considers their role in the history of the Assemblies of God throughout its institutionalization as a branch of the Pentecostal Protestantism present in Brazil as well as their struggle for recognition.